Kekuatan Lelah Baja Karbon dengan Lasan Alur Ganda V dan U - Herdi Susanto; Syurkarni Ali; M Taufik; Firman Yulitda (universitas teuku umar, 2015)
The case studies in the field, especially in the districts of Aceh Barat, if the shaft has been used fracture, then largely reconnected by means of welded, through welding without considering the type of groove welds suitable for welded joints pivot, so that its power will be lower and the life of the shaft becomes shorter. This study aims to determine the type of groove welds suitable for metal welding carbon steels are used and sold in the market town of Meulaboh, and estimate the maximum load permitted to work on the shaft so that the expected life of the shaft becomes longer, and see the pattern of fractures that occur on the surface shaft. Testing is done for 3 specimens a double groove welds V, 3 specimens double groove U and without welds 6 specimens in accordance with ASTM E-466. The results showed that specimens with a double weld groove U have a better fatigue strength compared with the double-groove weld V. fatigue limit (endurance limit) 85.83 MPa carbon steel. The pattern of the specimen surface faulting on the double U groove weld area deformed by the signs of the beach (beach mark) towards the center of the surface of the specimen (weld center) fracture pattern on the specimen surface area double V groove welds undergo large deformations on the outskirts of surface spesimen. Keywords : double-groove weld V, double-groove weld U, S-N Curve, Endurance limit, fracture pattern